2009
DOI: 10.1063/1.3212613
|View full text |Cite
|
Sign up to set email alerts
|

Layering of [BMIM]+-based ionic liquids at a charged sapphire interface

Abstract: The structure of two model room temperature ionic liquids, [BMIM](+)[PF(6)](-) and [BMIM](+)[BF(4)](-), near the solid/liquid interface with charged Al(2)O(3)(0001) (sapphire) was determined with subnanometer resolution by high energy (72.5 keV) x-ray reflectivity. [BMIM](+)[PF(6)](-) exhibits alternately charged, exponentially decaying, near-surface layering. By contrast, the smaller-anion compound, [BMIM](+)[BF(4)](-), shows only a single layer of enhanced electron density at the interface. The different lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
135
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 100 publications
5
135
0
Order By: Relevance
“…The two oscillatory terms are described by a distorted crystal model that mimics the decaying near-surface layering indicated by the presence of the finite-width dip. The distorted crystal model has been successfully used in many previous studies of liquid metals (3) and ILs (16,17). Refractive indices for the three parts were calculated from the NEXAFS spectra by the Kramers-Kronig transformation.…”
Section: Resultsmentioning
confidence: 99%
“…The two oscillatory terms are described by a distorted crystal model that mimics the decaying near-surface layering indicated by the presence of the finite-width dip. The distorted crystal model has been successfully used in many previous studies of liquid metals (3) and ILs (16,17). Refractive indices for the three parts were calculated from the NEXAFS spectra by the Kramers-Kronig transformation.…”
Section: Resultsmentioning
confidence: 99%
“…A rich library of nanostructures were observed both adsorbed onto [33][34][35][36][37] and near 33,36 solid interfaces, which revealed that previous descriptions based on data normal to the IL-solid interface were far too simplistic. [38][39][40][41] The nanostructure of the ion layer in contact with the substrate is strongly affected by the registry between the ions and surface adsorption sites, 13,[33][34][35][36][37] except when the cation is large and sterically hindered. 33 As in the bulk, near surface nanostructure is sensitive to both cation and anion type.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray reflectivity experiments on ͓bmim͔ + / ͓BF 4 ͔ − and ͓bmim͔ + / ͓PF 6 ͔ − provide details of the IL layering behavior at charged sapphire surfaces. 114 MD simulations of ͓bmim͔ + / ͓PF 6 ͔ − at a planar graphite surface showed that the preferred orientation of the aromatic cation is flat on the surface. 115 Rivera-Rubero and Baldelli 111 used SFG to detect the reorientation of ͓bmim͔ + cations at a Pt electrode as the potential was varied, and the effects are different depending on whether the anion is ͓BF 4 ͔ − or ͓PF 6 ͔ − .…”
Section: Il Interfacesmentioning
confidence: 99%
“…A wide variety of experimental, theoretical, and simulation methods have been applied to the study of ILs at interfaces. [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122] Santos and Baldelli 112 have used interfacial sumfrequency generation ͑SFG͒ to show that at IL interfaces with gases or vacuum, alkyl chains on either the cations or the anions extend from the surface into the gas or vacuum. Rutherford backscattering spectra for the ͓bmim͔ + / ͓PF 6 ͔ − -vacuum interface also show the cation butyl group protruding from the bulk liquid into vacuum.…”
Section: Il Interfacesmentioning
confidence: 99%